Original paperDosimetric analysis and clinical outcomes in CT-based mould brachytherapy in early oral cancers in patients unfit for surgery - Mukherji, Ashutosh; Mourougan, Sinnatamby; Saravannan, Kandasamy; Vivekanandam, Singhavajala; Reddy, K. Sathyanarayana (Journal of Contemporary Brachytherapy, 2015)
Purpose: Brachytherapy in the oral cavity is an important alternative to conventional treatment, and provides a high localized dose and short overall treatment time. A rapid fall of dose beyond radioactive source makes it possible for increased tumour control and sparing surrounding tissue, while short overall treatment duration reduces risk of tumour repopulation. Moulds are fabricated to hold the catheters in position as closely as possible to tumour surface to provide adequate dose coverage of tumour volume and increase distance to other normal surrounding structures. Image based planning and dose optimisation help in better defining target volume and dose coverage. Material and methods: A retrospective analysis of patients of early squamous cell carcinomas of lip and buccal mucosa from September 2011 to June 2014 to study response to mould brachytherapy. Double plane moulds were prepared for all lip cancer cases and single plane for buccal mucosa cases. Patients are being followed up till disease recurrence. In this study evaluation was done of the technique used, planning details, response to therapy, and reactions encountered. Results : Nine patients treated by mould therapy were reviewed; seven cases were of lip and two of buccal mucosal cancers. Dose delivered ranged from 12.5-48 Gy in fraction sizes of 2.5-3.5 Gy. Equivalent dose in 2 Gy fractions (EQD2) ranged from 18-64 Gy. Maximum dose to organs at risk (OAR) was 91% of prescribed dose. Local mucositis was only reaction in all cases, which resolved in 3-6 weeks. Median follow-up was 19 months. Eight out of nine patients are in remission at a minimum of 7 months (1 case, rest over 14 months) post therapy and only patient had nodal recurrence at 18 months. Conclusions : Mould therapy is an effective treatment method for selected early and superficial squamous cell carcinomas of the oral cavity, although indications are limited.